Prefrontal-Striatal Mechanisms of Behavioral Impulsivity During Consumption of Delayed Real Liquid Rewards - Misonou, Ayaka; Jimura, Koji (Frontiers in Behavioral Neuroscience, 2021)
Intertemporal choice involves evaluation of future rewards and reflects behavioral impulsivity. After choosing a delayed reward in an intertemporal choice, a behavioral agent waits for, receives, and then consumes the reward. The current study focused on the consumption of the delayed reward, and examined the neural mechanisms of behavioral impulsivity. In humans consuming delayed real liquid rewards in an intertemporal choice, the ventral striatum (VS) showed differential activity between anterior (aVS) and posterior (pVS) regions depending on the degree of behavioral impulsivity. Additionally, impulsive individuals showed activity in the anterior prefrontal cortex (aPFC). An analysis of task-related effective connectivity based on psychophysiological interaction (PPI) revealed that PPI was robust from the aPFC to pVS, but not in the opposite direction. On the other hand, strong bidirectional PPIs were observed between the aVS and pVS, but PPIs from the pVS to aVS were enhanced in impulsive individuals. These results suggest that behavioral impulsivity is reflected in aPFC-VS mechanisms during the consumption of delayed real liquid rewards.